Impacts of Corporate Social Responsibility on the Links between Green Marketing Awareness and Consumer Purchase Intentions - Norazah Mohd Suki; Norbayah Mohd Suki; Nur Shahirah Azman (2016)
This study examines the mediating roles of corporate social responsibility on the links between green marketing awareness and consumer purchase intentions. Data was analyzed using the partial least squares (PLS) approach for the analysis of structural equation models with SmartPLS computer program version 2.0. PLS results revealed that corporate social responsibility partially mediated the link between green marketing awareness and purchase intentions of the product. Consumers develop positive green marketing awareness based on the growing environmental knowledge. They were aware of the green marketing program of the retail store when they noticed that the store allocated specified space to sell eco-friendly products. Furthermore, the companies make their green marketing activities known to the publics by distributing eco-friendly fliers which helps to increase sales revenue, raise consumer awareness, and develop greater intention to purchase the products. The outcomes of the mediating effects of this study add a new momentum to the growing literature and preceding discoveries on consumer green marketing awareness, which is inadequately researched in the Malaysian setting.